Focus of pediatric surgical reports during the SARS-CoV-2 pandemic: A narrative review - Karina Miura da Costa; Thiago Elias Ferrari Khouri; Amulya Kumar Saxena (Wolters Kluwer Medknow Publications, 2022)
Background: Coronavirus disease-2019 (COVID-19) pandemic impacted surgical activity at health-care facilities and led to significant changes in the characteristics of publications in medical journals. This is a narrative review that outlines the focus of pediatric surgical reports during the ongoing COVID-19 pandemic. Methods: Publications on pediatric surgery during the pandemic were carefully reviewed, and data emerging from reports on COVID-19 were selected to address: (1) the impact of COVID-19 on pediatric surgical procedures; (2) children undergoing surgical intervention; and (3) expansion of telemedicine. Results: Regarding surgical activity in tertiary hospitals, there was a reduction in the number of elective surgeries, with reports of an increase in complicated appendicitis and in testicular torsions with symptoms for more than 6 h. The pandemic impacted specific surgical fields, with reports on trauma, appendectomies, urology, cardiac surgery, and kidney transplant. In children positive for COVID-19 that underwent surgery, postoperative complications were more indicative of the primary surgical pathology and there were no postoperative deaths. In a report of universal screening, <1% of children had positive reverse transcription-polymerase chain reaction (RT-PCR). In a report addressing telemedicine during the pandemic, it was well evaluated by both pediatric surgeons and patients' families, but most surgical departments did not provide the service. Conclusions: The pandemic brought significant changes in surgical care. As expected, there was a reduction in elective surgeries, RT-PCR-positive children did not present worse postoperative outcomes than negative ones but there is still a paucity of data regarding COVID-19 children, and telemedicine may play an important role in health care, especially in times of social distancing.